Special situations: Intradialytic hypertension/chronic hypertension and intradialytic hypotension. Issue 6 (30th June 2017) - Van Buren, Peter Noel; Inrig, Jula K.
Abstract: Hypertension is a comorbidity that is present in the majority of end‐stage renal disease patients on maintenance hemodialysis. This population is particularly unique because of the dynamic nature of blood pressure (BP) during dialysis. Modest BP decreases are expected in most hemodialysis patients, but intradialytic hypotension and intradialytic hypertension are two special situations that deviate from this as either an exaggerated or paradoxical response to the dialysis procedure. Both of these phenomena are particularly important because they are associated with increased mortality risk compared to patients with modest decreases in BP during dialysis. While the detailed pathophysiology is complex, intradialytic hypotension occurs more often in patients prescribed fast ultrafiltration rates, and reducing this rate is recommended in patients that regularly exhibit this pattern. Patients with intradialytic hypertension have a poorly explained increase in vascular resistance during dialysis, but the consistent associations with extracellular volume overload point toward more aggressive fluid management as the initial management choices for these patients. This up to date review provides the most recent evidence supporting these recommendations as well as the most up to date epidemiologic and mechanistic research studies that have added to this area of dialysis management.